2012
DOI: 10.1590/s1982-45132012000200014
|View full text |Cite
|
Sign up to set email alerts
|

Comparação do estoque de C estimado em pastagens e vegetação nativa de Cerrado

Abstract: Prof. Dr. do Instituto de Geografia-UFU. Bolsista CNPq. rrosa@ufu.br RESUMO:As mudanças climáticas constituem uma ameaça para o meio ambiente e para o desenvolvimento sustentável no mundo. -1 e a pastagem degradada 27,51 Mg C ha -1 , o que permite concluir que pastagens bem estabelecidas e manejadas, podem contribuir no aumento da taxa de sequestro de carbono pelo solo. Entretanto, a falta de correção do solo, de adubação de manutenção, de controle de processos erosivos e de manejo adequado, com excesso de lot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Based on the Digital Atlas of Brazilian Pastures, in 2019, 51% of the pasture areas in the state of Bahia were classified as «severe degradation» Brazil has approximately 41 million hectares of degraded pasture, which directly affects the health of vegetation and soil and disturbs carbon absorption. An analysis in the Cerrado biome compared the carbon stock between improved brachiaria grassland, degraded brachiaria grassland and savanna areas and showed that improved grassland areas store more carbon in more than half of the value found for degraded grassland, while for the savanna, the carbon stock values were close to those of improved brachiaria grassland (Rosendo and Rosa, 2012). These results highlight the importance of conservation and the need for proper management of cultivated areas for carbon flux.…”
Section: Spatial and Temporal Dynamics Of Net Primary Productionmentioning
confidence: 84%
“…Based on the Digital Atlas of Brazilian Pastures, in 2019, 51% of the pasture areas in the state of Bahia were classified as «severe degradation» Brazil has approximately 41 million hectares of degraded pasture, which directly affects the health of vegetation and soil and disturbs carbon absorption. An analysis in the Cerrado biome compared the carbon stock between improved brachiaria grassland, degraded brachiaria grassland and savanna areas and showed that improved grassland areas store more carbon in more than half of the value found for degraded grassland, while for the savanna, the carbon stock values were close to those of improved brachiaria grassland (Rosendo and Rosa, 2012). These results highlight the importance of conservation and the need for proper management of cultivated areas for carbon flux.…”
Section: Spatial and Temporal Dynamics Of Net Primary Productionmentioning
confidence: 84%
“…All studied fish farms are located in the hydrographic basin of the Araguari River, Minas Gerais, Brazil (Figure 1). Source: Adapted from Rosendo and Rosa (2012). Research, Society and Development, v. 10, n. 11, e40101119332, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i11.19332…”
Section: Methodsmentioning
confidence: 99%
“…Further, pastures can play an essential role in the environmental context, especially considering their potential to sequester atmospheric carbon, being a carbon stock in the soil. In some cases, not degraded pastures can be more efficient than natural systems, concerning carbon stock (ROSENDO; ROSA, 2012). These pasture areas also contribute to animal protein production, with Brazil leading the world's largest meat producer's rank.…”
Section: Introductionmentioning
confidence: 99%